67Cu-Radiolabeling of a multimeric RGD peptide for αVβ3 integrin-targeted radionuclide therapy: stability, therapeutic efficacy, and safety studies in mice. Issue 4 (April 2017) - Jin, Zhao-Hui; Furukawa, Takako; Ohya, Tomoyuki; Degardin, Mélissa; Sugyo, Aya; Tsuji, Atsushi B.; Fujibayashi, Yasuhisa; Zhang, Ming-Rong; Higashi, Tatsuya; Boturyn, Didier; Dumy, Pascal; Saga, Tsuneo
Abstract : Objective: Copper-67 ( 67 Cu) is one of the most promising radionuclides for internal radiation therapy. Globally, several projects have recently been initiated for developing innovative approaches for the large-scale production of 67 Cu. Encouraged by these, we performed 67 Cu-radiolabeling of a tetrameric cyclic Arg–Gly–Asp (cRGD) peptide conjugate, cyclam-RAFT-c(-RGDfK-)4, which selectively targets αV β3 integrin (αV β3 ), the transmembrane receptor involved in tumor invasion, angiogenesis, and metastasis. We also evaluated the therapeutic potential and safety of this radiocompound. Materials and methods: 67 Cu, produced through the 64 Ni(α, p) 67 Cu reaction, was used for the radiolabeling of cyclam-RAFT-c(-RGDfK-)4 at 70°C for 10 min. The radiolabeling efficiency and product stability were assessed using reversed-phase high-performance liquid chromatography and/or thin-layer chromatography. Mice with subcutaneous αV β3 -positive U87MG-glioblastoma xenografts received a single intravenous injection of one of the following: 67 Cu-cyclam-RAFT-c(-RGDfK-)4 (11.1 MBq), peptide control, or vehicle solution. The tumor volumes were measured, side effects were assessed in terms of body weight, routine hematology, and hepatic and renal functions, and the mouse radiation dosimetry was estimated. Results: 67 Cu-cyclam-RAFT-c(-RGDfK-)4 was produced with a radiochemical purity of 97.9±2.4% and a specific activity of 2.7±0.6 MBq/nmol and showed high in-vitro and in-vivo plasma stability. The administration of a single dose of 67 Cu-cyclam-RAFT-c(-RGDfK-)4 resulted in significant tumor growth delay in comparison with that observed upon vehicle or peptide control administration, with an estimated tumor-absorbed dose of 0.712 Gy. No significant toxicity was observed in 67 Cu-cyclam-RAFT-c(-RGDfK-)4 -treated mice. Conclusion: 67 Cu-cyclam-RAFT-c(-RGDfK-)4 would be a promising therapeutic agent for αV β3 integrin-targeted internal radiotherapy. Abstract : Supplemental Digital Content is available in the text.